Bacterial diversity and community structure during fermentation of Chinese sauerkraut with Lactobacillus casei 11MZ‐5‐1 by Illumina Miseq sequencing. (11th December 2017) - Du, R.; Ge, J.; Zhao, D.; Sun, J.; Ping, W.; Song, G.
Abstract: The bacterial diversity and community structure involved in Chinese sauerkraut is one of the most important factors shaping the final characteristics of traditional foods. In this research, Lactobacillus casei 11MZ‐5‐1 was applied in Chinese sauerkraut fermentation as a starter culture. Illumina Miseq sequencing analysis was used to reveal the bacterial diversity and community structure during Chinese sauerkraut fermentation. A total of 177 283 high‐quality reads of 16S rRNA V4 regions were obtained. The inoculation of L. casei 11MZ‐5‐1 decreased considerably the bacterial richness and bacterial diversity. This inoculum led to the replacement of Lactococcus by Lactobacillus . The levels of Pseudomonas and Enterobacter bacteria decreased. These findings reveal the evolution of important bacterial groups that are involved in fermentation and will facilitate improvements in the Chinese sauerkraut fermentation process. Significance and Impact of the Study: This research thoroughly revealed the effects of Lactobacillus casei 11MZ‐5‐1 starter cultures on bacterial communities during Chinese sauerkraut fermentation. Illumina Miseq sequencing was effective technique to monitor the bacterial diversity and community structure. The inoculation of L. casei 11MZ‐5‐1 led to the decline of bacterial richness and diversity together with a consistent predominance of Lactobacillus during spontaneous fermentation. The result collectively suggested L. casei 11MZ‐5‐1 is a promising starter in Chinese sauerkraut manufacturing. Abstract : Significance and Impact of the Study This research thoroughly revealed the effects of Lactobacillus casei 11MZ‐5‐1 starter cultures on bacterial communities during Chinese sauerkraut fermentation. Illumina Miseq sequencing was effective technique to monitor the bacterial diversity and community structure. The inoculation of L. casei 11MZ‐5‐1 led to the decline of bacterial richness and diversity together with a consistent predominance of Lactobacillus during spontaneous fermentation. The result collectively suggested L. casei 11MZ‐5‐1 is a promising starter in Chinese sauerkraut manufacturing.